2020
DOI: 10.1016/j.tranon.2020.100869
|View full text |Cite
|
Sign up to set email alerts
|

A novel vitamin D gene therapy for acute myeloid leukemia

Abstract: Current treatment approaches for older adult patients with acute myeloid leukemia (AML) are often toxic and lack efficacy. Active vitamin D3 (1,25(OH) 2 D3) has been shown to induce myeloid blast differentiation but at concentrations that have resulted in unacceptable, off-target hypercalcemia in clinical trials. In our study, we found that the combination of 1,25(OH) 2 D3 and the hypomethylating agent (HMA) 5-Azacytidine (AZA) enhanced cytotoxicity and differentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Through in vitro studies with different cell lines, multiple pathways and signals are proof related to AML cell differentiation and can be affected by VDR [ 123 , 124 ]. These were also proofed in some in vivo studies with mice and further confirmed the possibility of increasing survival within mice [ 125 , 126 , 127 , 128 , 129 ]. Regarding clinical experience, there was no inspiring development in this field.…”
Section: Application Of Natural Products In Aml Therapymentioning
confidence: 54%
See 1 more Smart Citation
“…Through in vitro studies with different cell lines, multiple pathways and signals are proof related to AML cell differentiation and can be affected by VDR [ 123 , 124 ]. These were also proofed in some in vivo studies with mice and further confirmed the possibility of increasing survival within mice [ 125 , 126 , 127 , 128 , 129 ]. Regarding clinical experience, there was no inspiring development in this field.…”
Section: Application Of Natural Products In Aml Therapymentioning
confidence: 54%
“…However, the limitation of vitamin D-affect therapy is the need for high concentration of vitamin D to reach therapeutic effect, which might cause systemic side effects [ 134 , 135 , 136 ]. Several methods are possible to overcome the barriers we face currently, including possible oral supplementation [ 132 ], select patient according to receptor polymorphisms [ 137 ], gene therapy involving CYP27B1 treatment [ 126 ].…”
Section: Application Of Natural Products In Aml Therapymentioning
confidence: 99%
“…Some of the earliest life forms such as phytoplankton took advantage of sunlight to photosynthesize 2 metabolites for energy and survival: glucose and vitamin D [ 8 ]. Our recent study demonstrated that the combination of 1,25VD3 and 5-Azacytidine (a FDA-approved hypomethylating agent) enhanced cytotoxicity/differentiation and inhibited proliferation of AML blasts in vivo [ 9 ]. Up to 35% of AML patients have mutations in the FMS-like receptor tyrosine kinase 3 (FLT3) gene and defective protein products (AML-FLT3) that are associated with poorer survival through an increased risk of relapse [ 10 ].…”
mentioning
confidence: 99%
“…First, we performed transcriptome analyses (RNA-seq) of 4 different AML-FLT3 cell lines including MV4–11, MOLM-14, MV4–11-midostaurin-resistant cells and MOLM-14-midostaurin-resistant cells which were previously reported [ 9 ]. Among many differential expression methods developed for RNA-seq data analyses, FPKM number was found to be one of the best approaches in precision and accuracy on reporting RNA-seq results [ 16 ].…”
mentioning
confidence: 99%
“…27 This is consistent with data we observed in our study that SLE patients presenting with more severe COVID-19 chest symptoms had lower levels of vitamin D. The critical role of vitamin D can be also observed in certain malignancies, and vitamin D requires CYP27B1 to create active vitamin D. In a study of type of bone marrow (BM) malignancy cells, the authors noticed considerably minimal levels of CYP27B1 proteins within BM cells compared to non-AML individuals. 43 Current guidelines have suggested a target level of 30 to 40 ng/mL for cases with a possibility of fractures, falling, autoimmune disorders, and malignant tumors. The recommended dose of vitamin D therapy is <10,000 IU per day with a target 25-hydroxyvitamin D level of 30 ng/mL or more for affected cases.…”
Section: Discussionmentioning
confidence: 99%